088 Comparison of cardiovascular magnetic resonance stress perfusion with single photon emission CT (SPECT) in patients with left main stem disease: a CE-MARC substudy. (16th May 2012) - Greenwood, J P; Kidambi, A; Zaman, A; Maredia, N; Motwani, M; Dickinson, C J; Brown, J M; Nixon, J; Everett, C C; Ball, S G; Plein, S
Abstract : Introduction: Approximately 5% of patients with stable angina have disease of the left main stem (LMS). Three-year survival in patients with >50% LMS stenosis may be as low as 50%. Single photon emission tomography (SPECT) fails to detect ischaemia in up to 15% of LMS stenoses, and identification of the "classical" pattern of both left anterior descending (LAD) and circumflex (LCx) coronary territory ischaemia is lower still. To date, the utility of cardiovascular magnetic resonance (CMR) perfusion in LMS disease is poorly established. The CE-MARC study was a prospective study of 752 patients with suspected coronary artery disease, enrolled to undergo CMR, SPECT and x-ray coronary angiography; we assessed the diagnostic performance of SPECT and CMR to detect LMS disease. Methods: All patients with LMS disease ≥50% on quantitative angiography were identified from the CE-MARC study. All patients had undergone adenosine stress perfusion by CMR and SPECT and also invasive x-ray angiography.1 We compared detection rates for visual perfusion analysis from both the CMR and SPECT perfusion studies in patients with ≥50% and ≥70% LMS stenosis on angiography. Results: Of 23 patients in the CE-MARC cohort with LMS stenosis ≥50%, one patient could not be analysed. CMR identified evidence of inducible perfusion defects in 18/22 (82%) of the LMS group; SPECT identified 13/22 (59%). For CMR and SPECT respectively, inducible perfusion defects were found in both LAD and LCx territories for 6/18 (33%) and 2/13 (15%). Only one patient had normal perfusion analyses (false negative) for both CMR and SPECT. Of 11 patients with ≥70% LMS stenosis, 10 (91%) had inducible perfusion defects with CMR vs 5 (45%) with SPECT. Six (55%) vs 2 (18%) had a LAD and LCx disease pattern. Perfusion abnormalities were detected with similar frequency in ≥50% and ≥70% groups by both CMR (p=0.64) and SPECT (p=0.49). Abstract 088 figures 1 and 2 summarise the detection rate of CMR and SPECT in LMS disease in the ≥50% and ≥70% LMS groups respectively. Conclusions: CMR stress perfusion imaging identifies ischaemia in a higher proportion of patients with significant LMS disease than SPECT, and identifies a "classical" LMS pattern with higher frequency. Perfusion abnormalities are detected with similar frequency in patients with ≥50% and ≥70% LMS stenosis.